2007
DOI: 10.1128/cvi.00133-07
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Anthroponotic Cutaneous Leishmaniasis (ACL) Caused byLeishmania tropicain Sanliurfa Province, Turkey, Where ACL Is Highly Endemic

Abstract: In this study, we aimed to evaluate the validity of the conventional enzyme-linked immunosorbent assay (ELISA) and the Western blotting test for the diagnosis of anthroponotic cutaneous leishmaniasis (ACL) using serum samples obtained from 51 patients with parasitologically proven nontreated CL (NonT-CL patients) and 62 patients under treatment for CL (UT-CL patients). Additionally, 29 serum samples obtained from patients with parasitologically and serologically proven visceral leishmaniasis (VL) were also use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 38 publications
7
31
1
2
Order By: Relevance
“…Reactions with 15 bands ranging from 17-92 kDa were observed. Of these bands, 8 (17,20,21,23,25,30,37, and 53 kDa) were also observed with sera from EI hyraxes and PCR-positive humans, suggesting that the appearance of antibodies against these antigens is indicative of exposure to L. tropica in both species. Reaction to each band was assessed according to its mean net intensity value using the Kodak 1D computerized program as previously described.…”
Section: Western Blotmentioning
confidence: 98%
See 3 more Smart Citations
“…Reactions with 15 bands ranging from 17-92 kDa were observed. Of these bands, 8 (17,20,21,23,25,30,37, and 53 kDa) were also observed with sera from EI hyraxes and PCR-positive humans, suggesting that the appearance of antibodies against these antigens is indicative of exposure to L. tropica in both species. Reaction to each band was assessed according to its mean net intensity value using the Kodak 1D computerized program as previously described.…”
Section: Western Blotmentioning
confidence: 98%
“…Although serological studies of antibody responses have not been reported previously with hyraxes, it has been used for the diagnosis and study of L. tropica CL. 29,37 Several of the antigens, 17, 20, 21, 23, 25, 30, 37, and 53 kDa, recognized both by infected hyrax and human serum show molecular weights similar to those used in the serodiagnosis of L. tropica CL (27 and 30 kDa), or for monitoring treatment (19 kDa). 37 Thus, hyrax antibody reactivity to specific L. tropica antigens resembles the response mounted by infected humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their use is not routine in the Old World due to variable or low sensitivity in endemic countries [106,107]. The sensitivity of ELISA in the Old World reached 60% with L. major, though a recent study from Turkey demonstrated a sensitivity of 88% with L. tropica [108,109]. In the New World, IFAT showed a sensitivity of 27.7% for CL and 56.7% for MCL with L. braziliensis [110].…”
Section: Serological Techniquesmentioning
confidence: 99%